Plan Vallejo aplicado a UNE EPM Telecomunicaciones S.A. (2012)
This paper analyzes the importance of applying the Plan Vallejo’s export service incentive to UNE EPM Telecomunicaciones S.A. for equipment import. The document describes the main features and demands, as well as its benefits of such a figure in order to leave a written-public document to be reached by all technical areas of the company which are responsible to request equipments and components to lend excellent telecommunication services.